Optimisation of helium-assisted drone : control and flight analysis - See, Kelwin Chun Gan (Nanyang Technological University, 2020)
Recent developments in technology has led to an increased interest in drones and their applications, as well as widespread usage. While certain industries have managed to exploit the usage of drones to a large degree, applications in other areas such as Human Aid and Disaster Relief has immense potential for drone applications. The challenge of using drones in such areas are its low endurance and payload. Endurance is critical especially for drones that are required for surveillance and delivery, and even more important for those operating in disaster relief. Therefore, the project seeks to increase endurance by incorporating helium into the drone to provide static lift. This will be done by modifying and redesigning existing drone structures to incorporate balloons inflated with helium. As such, the effects of incorporating such structures on the drone will be investigated. An experiment on the effects of having a pair toroidal shape balloon around the rotor on the thrust will be conducted, with simulation done to find possible ways to optimise such effects. In the process of experimentation and simulation, a prototype will be built for a flight test and suggestions to be made for further works will be discussed.